2007
DOI: 10.1002/app.26297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TRITON™ X‐based dispersants bearing a carboxylic terminal group on rheological properties of BAM/ethyl cellulose/terpineol paste

Abstract: In this study, we attempted to use TRI-TON TM X (or octyl phenol ethoxylate (OPE) of different oxyethylene units (i.e., n ¼ 2, 5, and 10))-based dispersants containing a carboxylic group in the oxyethylene chain end for the formulation of BAM phosphor paste. Thus, a threecomponent system employing OPE-COOH as a dispersant, terpineol as a solvent, and ethyl cellulose as a binder was compounded with BAM particles, and the rheological properties of the paste were investigated in detail. Among three acidic TRITON … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…The synthesis and characterization of Triton X derivatives containing specially added acidic or basic moieties were reported earlier by our group 11. We also demonstrated that a Triton X based compound with a terminal carboxylic acid (OPE–COOH) could be a better dispersant than others that have ester, phosphoric acid, or amino‐functional groups 12. The added carboxylic terminal group provides a strong interaction with the surface of a commonly used blue phosphor when dispersed in terpineol as a solvent.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…The synthesis and characterization of Triton X derivatives containing specially added acidic or basic moieties were reported earlier by our group 11. We also demonstrated that a Triton X based compound with a terminal carboxylic acid (OPE–COOH) could be a better dispersant than others that have ester, phosphoric acid, or amino‐functional groups 12. The added carboxylic terminal group provides a strong interaction with the surface of a commonly used blue phosphor when dispersed in terpineol as a solvent.…”
Section: Introductionsupporting
confidence: 58%
“…The isoelectric point of BAM phosphor is 10.27 12. In the course of the acidic titration, the ζ potential value of BAM phosphor increases (at pH = 2, the ζ potential is 162 mV).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, poly‐(oxyethylene) isooctylphenyl ether (X‐100) dispersant usually is used to disperse inorganic powders, e.g., nano lead zirconate titanate (PZT) powder, barium titanate nano powder (BaTiO 3 ), yttrium oxide/zirconium oxide (Y 2 O 3 /ZrO 2 ) powders, slurries, multiwall carbon nanotubes (MWCNTs), single‐walled carbon nanotubes (SWNTs), and nanocrystal indium tin oxide (ITO) particles . Other dispersants, such as tert‐ octylphenoxypoly(ethoxyethanol) (X‐114), also are used to disperse ZrO 2 particles, yttria‐stabilized zirconia (TZ‐3Y) powders, and phosphor . X‐100 also is used in the field of biotechnology, such as its use in the separation of protein from cell membranes and extracting DNA .…”
Section: Introductionmentioning
confidence: 99%
“…In our group, various types of sophisticated dispersants (e.g., Triton derivatives) are often employed as a viscosity modifying agent. 9,10 Synthesized acrylic dispersants with well-defined compositions have captivated both academic and industrial polymer engineers. Recent works have been done to improve the modification of classical syntheses toward more precisely controlled acrylic backbones, which are required in the design of advanced dispersants.…”
Section: Introductionmentioning
confidence: 99%